2021
DOI: 10.1111/apa.15765
|View full text |Cite
|
Sign up to set email alerts
|

Secondary immune thrombocytopenia in children: Characteristics and outcome of a large cohort from two Spanish centres

Abstract: Aim: To evaluate the incidence and outcome of secondary immune thrombocytopenia (ITP) in a large cohort of paediatric Spanish patients. Methods: A retrospective observational study was conducted in two paediatricUniversity hospitals in Spain between 2009 and 2019, which included children from 4 months to 18 years old diagnosed with ITP. Data were recorded from clinical charts: gender, age at diagnosis, coexisting condition and associated characteristics, outcome and treatment.Results: Secondary ITP was diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…One study conducted on a numerous cohort of pediatric ITP patients, identified that the two most frequent causes of secondary ITP cases are recent immunizations and viral infections, followed by autoimmune disorders and immunodeficiency [16]. Within this study, post-immunization and post-viral infections ITPs showed the best remission rates [16]. Although H. pylori infection is usually acquired during childhood, physicians are less familiar with its extra-gastric, hematological manifestations.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…One study conducted on a numerous cohort of pediatric ITP patients, identified that the two most frequent causes of secondary ITP cases are recent immunizations and viral infections, followed by autoimmune disorders and immunodeficiency [16]. Within this study, post-immunization and post-viral infections ITPs showed the best remission rates [16]. Although H. pylori infection is usually acquired during childhood, physicians are less familiar with its extra-gastric, hematological manifestations.…”
Section: Discussionmentioning
confidence: 83%
“…In children in particular, search for a secondary cause of ITP and treatment of possible causative agents could represent an important therapeutic aid which can lead to avoidance of standard treatment and its widely known side effects, which are more extensive at this particular age group [68]. One study conducted on a numerous cohort of pediatric ITP patients, identified that the two most frequent causes of secondary ITP cases are recent immunizations and viral infections, followed by autoimmune disorders and immunodeficiency [16]. Within this study, post-immunization and post-viral infections ITPs showed the best remission rates [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, children diagnosed with primary ITP may, in the future, develop to autoimmune disease (AID) or haematological disease, such as systemic lupus erythematosus (SLE) and aplastic anaemia (AA). 8,[11][12][13][14] Studies on the development of diseases in children with primary ITP are limited. A prospective study conducted by Schifferli et al reported that among 13 (13/44, 29.5%) children with positive ANA,…”
Section: Introductionmentioning
confidence: 99%